Evaluation of the modulation transfer function of a high energy X-ray tomograph; Неразрушающий контроль: электронное приборостроение, технологии, безопасность; Т. 2 - Mamyrbaev T. A. Talgat Askarbekovich (Electrical Engineering and Non-Destructive Testing, 2015)
Заглавие с титульного экрана